Seasonal occurrence of pests and predators in growing watermelon (Citrullus lanatus) (Thunb.) in La Molina - Ccahuana, Daniel (2020)
Observations were made to determine the seasonal occurrence of Diaphania nitidalis (Stoll), Prodiplosis longifila (Gagne), Liriomyza huidobrensis (Blanchard), Bemisia tabaci (Gennadius), Aphis gossypii (Glover), Agrotis ipsilon (Hufn.) Spodoptera ochrea (Hampson) and their natural enemies in watermelon’s crop. located in the Agrarian University of La Molina were made the land called Field Free I of 1 ha. It was divided into five sectors in which were taken randomly 5 plants per sector, there were evaluated 25 plants in total. On each plant four outbreaks were recorded, 4 sheets randomly, as the foliage of the plant, 4 flowers and 4 fruits distributed throughout the plant, the neck of the plant and 2 meters of furrow by sector. The earth worm Agrotys ipsilon (Lepidoptera: Noctuidae) did not cause major damage. As for Diaphania nitidalis (Stoll) (Lepidoptera: Crambidae) infestation was low in the first months of the crop (January, February and March); however, in the month of April they increased records of individuals in buds, flowers and fruits. It should be noted the presence of Spodoptera ochrea (Hampson) (Lepidoptera: Noctuidae) who did affect significantly during the stages of vegetative growth, flowering and fruiting; infesting leaves, flowers and fruits. They were registered as natural enemies Chrysoperla externa (Hagen) and Cycloneda sanguinea (Linnaeus).